The position of Distance Education in a journal network. Issue 4 (2nd October 2019) - Zawacki-Richter, Olaf; Buntins, Katja
ABSTRACT: On the occasion of the 40th anniversary of the journal Distance Education (DE), this study explores the position of this journal in a network of open and distance education, educational technology and learning design publications. A citation network analysis was undertaken to explore the scholarly communication network of distance education, using articles published in DE from 1980 onwards ( n = 656), alongside references cited in those articles ( n = 16, 729), as well as articles ( n = 6003) and associated references ( n = 164, 444) published in 22 leading journals indexed in the Web of Science between 2014 and 2019. A distinction is made between a narrower (intra-DE) and a wider (inter-journal) distance education network. The study reveals DE's relationship to the wider educational technology community over time and identifies the most prolific journals and authors in this network.